The use of progeroid DNA repair-deficient mice for assessing anti-aging compounds, illustrating the benefits of nicotinamide riboside - Birkisdóttir, María B.; van Galen, Ivar; Brandt, Renata M. C.; Barnhoorn, Sander; van Vliet, Nicole; van Dijk, Claire; Nagarajah, Bhawani; Imholz, Sandra; van Oostrom, Conny T.; Reiling, Erwin; Gyenis, Ákos; Mastroberardino, Pier G.; et al. (Frontiers in Aging, 2022)
Despite efficient repair, DNA damage inevitably accumulates with time affecting proper cell function and viability, thereby driving systemic aging. Interventions that either prevent DNA damage or enhance DNA repair are thus likely to extend health- and lifespan across species. However, effective genome-protecting compounds are largely lacking. Here, we use Ercc1/- and Xpg-/- DNA repair-deficient mutants as two bona fide accelerated aging mouse models to test propitious anti-aging pharmaceutical interventions. Ercc1/- and Xpg-/- mice show shortened lifespan with accelerated aging across numerous organs and tissues. Previously, we demonstrated that a well-established anti-aging intervention, dietary restriction, reduced DNA damage, and dramatically improved healthspan, strongly extended lifespan, and delayed all aging pathology investigated. Here, we further utilize the short lifespan and early onset of signs of neurological degeneration in Ercc1/- and Xpg-/- mice to test compounds that influence nutrient sensing (metformin, acarbose, resveratrol), inflammation (aspirin, ibuprofen), mitochondrial processes (idebenone, sodium nitrate, dichloroacetate), glucose homeostasis (trehalose, GlcNAc) and nicotinamide adenine dinucleotide (NAD+) metabolism. While some of the compounds have shown anti-aging features in WT animals, most of them failed to significantly alter lifespan or features of neurodegeneration of our mice. The two NAD+ precursors; nicotinamide riboside (NR) and nicotinic acid (NA), did however induce benefits, consistent with the role of NAD+ in facilitating DNA damage repair. Together, our results illustrate the applicability of short-lived repair mutants for systematic screening of anti-aging interventions capable of reducing DNA damage accumulation.